(untitled) (Research, Society and Development, 2021)
Cervical cancer is a malignant neoplasm, which occupies a prominent place, drawing the attention of the scientific community, the medical and governmental authorities of several countries, particularly Brazil. Given the high prevalence rates of cervical cancer in the female population, periodic Pap smear is considered the best strategy for its prevention. The objective of this study is to report an experience of students of the nursing course that took place in a Family Health Strategy (FHS) unit in the city of Belém, which occurred through the performance of a health education activity on PAP. This is a descriptive study with a qualitative approach, of the experience report type, where the adopted methodology passed through the Theory of Problematization through the use of the Maguerez Arch. It became evident that some of the participating women were unaware of the examination, others already knew of its existence, but still did not understand the importance of its performance, among the participants, few had already performed the examination, but still had some doubts about it. It was bought from this article that the objective of the action was achieved, since the women who participated in these activities were sensitized as to the relevance of the exam, as well as about the autonomy in health and the importance of diligent and effective self-care. maintaining quality of life.